CURRENT STRATEGIES FOR PREVENTION AND MANAGEMENT OF ICU-ACQUIRED WEAKNESS IN CRITICALLY ILL PATIENTS: EVIDENCE, LIMITATIONS AND CLINICAL APPLICABILITY - A NARRATIVE REVIEW - Suchecka, Julia; Nesterak, Wiktor; Szubert, Izabela; Lamorski, Jakub; Stępień, Gabriela; Chudecka, Karolina; Chylewski, Michał; Józwa, Katarzyna; Kędzierska, Aleksandra; Przewoźna, Urszula (International Journal of Innovative Technologies in Social Science, 2026)
Intensive care unit-acquired weakness (ICU-AW) is a common complication of critical illness, defined as generalized, symmetrical muscle weakness developing during ICU stay that cannot be explained by pre-existing neuromuscular disorders. It is associated with prolonged mechanical ventilation, delayed recovery, and impaired long-term functional outcomes. The objective of this narrative review was to summarize current evidence on strategies for the prevention and early management of ICU-AW, with a particular focus on their effectiveness, limitations, and clinical applicability.A structured literature search was conducted using PubMed, MEDLINE, and Google Scholar databases, focusing on randomized controlled trials, systematic reviews, and meta-analyses published between 2018 and 2026. Particular attention was given to early mobilization, nutritional support, neuromuscular electrical stimulation (NMES), sedation strategies, and methods for assessing muscle status.Current evidence suggests that ICU-AW results from multiple interacting factors, including systemic inflammation, metabolic disturbances, immobilization, and inadequate nutritional support. Early mobilization remains the most consistently supported intervention, while nutritional therapy and NMES may provide additional benefits, particularly in selected patient populations. Monitoring of muscle status may facilitate early detection and guide clinical decision-making.Individual strategies for the prevention and early management of ICU-AW have important limitations when used in isolation. The available evidence suggests that different approaches may have complementary effects, although their combined impact remains incompletely understood. Further research is needed to better define optimal intervention strategies, including their timing, combination, and applicability in diverse patient populations.